Needs Assessment in Quality Improvement Management in Vocational Education (Case Study in Southwest Sumba, Indonesia) - Achmad Zaki Yamani; Aiza Yudha Pratama; Ade Yanyan Ramdhani; Galih Putra Pamungkas (Journal Of Resource Management, Economics And Business, 2022)
Purpose: The existing vocational education resources in Southwest Sumba do not yet have the appropriate quality, both from the aspect of collaboration to the output produced, in terms of graduates from related vocational education. Therefore, an approach related to needs assessment is needed to obtain input related to the quality development of vocational education from all stakeholders involved. Research Methodology: To provide improvement suggestions to enhance the quality of vocational education, this study conducted a needs assessment which was carried out using desk reviews, focus group discussions, interviews, and field observations and involved various stakeholders come from regulators, implementers, and vocational education graduates’ users. Results: Based on the needs assessment that has been conducted, four main problems were found, including the number of irrelevant vocational education institutions with the needs, a limited number of local industries as graduates' users, less government commitment as a regulator, and less quality of graduated. Several solutions can be applied, such as creating a partnership forum with industries, enabling the internship opportunity, developing a skill development center, and implementing a teaching factory at existing vocational education. Limitations: In this study, the involved stakeholders in the assessment tend to be incomplete, where students' perspectives as a product of vocational education cannot be accommodated and concluded properly. Contribution: This research hopefully can be a reference in quality improvement management, especially in vocational education, and beneficial for vocational education development and, in a broad sense, education.